The level of Anxiety in Cervical Cancer Patients of Lower Socioeconomic Status Receiving Chemoteraphy in RSUD Dr. Moewardi - Yolanda, Albina Eva; Karwur, Ferry Fredy (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2013)
Chemotheraphy for cervical cancer can result in physical and psychological side effects. One of the physical effects is anxiety. This study aimed at identifyingthe level of anxiety in cervical cancer patients of lower socioeconomic status receiving chemotherapy. The anxiety assessment was based on the physicaland psychological quetionnaire (HRS-A) with a guided interview with 40 patients of RSUD Dr. Moewardi. The data from the respondents were tabulatedand analyzed using pivot table of Microsoft Ecxel. The result showed that 40% of the respondents had anxiety symtoms, 30% had a mid anxiety and20% had a medium anxiety and 10% had a severe anxiety. Patients with a personal budget tend to have a higher anxiety compared with those who had agovernment health insurance (JAMKESMAS/Public Health Coverage Insurance). There had been several concerns among the patients including 1) thefear of side effect of chemotheraphy, 2) pessimism of the treatment outcome and the thought of death, 3) inconvenience of regular check for chemoteraphyto hospital and concern about the children and family. The level of anxiety varied among respondents. A lower socioeconic status, lower level of educationand the local wisdom of ‘nrimo’ were responsible for the abcence or lower level of anxiety symptoms in some patients.